O ensino de gêneros na proposta dos Parâmetros Curriculares Nacionais (PCN): a visão do professor - Teixeira, Rosimeire Boschesi (2008)
In this research had intended to see how the text has been working in the practices of education, consider whether this work follows, or not, the particulars of the National Curricular Parameters (PCN) and investigate how the teachers understand and apply the recommendations of the document, regarding the teaching of production in a textual approach of genres. According to the document, the text must be the basic unit of education and should be worked on their size discursive. Our intention was to promote a discussion on education genres in the proposal of CPN (1998), we believe that there was a change in focus of education in Brazil, from the publication of such material, until then returned to mainstream education and the excessive use of grammar legislation. To achieve the goals outlined, we opt for a qualitative research, conducting interviews with six informants: two teachers from the public network that operate in state educational workshop; two that, as well as act in the classroom, are militants of the union (APEOESP) and two who work in the classrooms of elementary school II. With the results, we find that the professional education are difficulties in implementation and understanding of the proposal suggested by the CPN (1998) with regard to their theoretical approaches. With respect to what problematized over the development of this study, and has been the object of constant concerns in education, the change is effective or not the pedagogical practice. While it is impossible to say with certainty that the practice of teachers has changed, it is possible to infer, at least in relation to the group of teachers informants, that there is a concern, a movement and a constant effort not to keep the Portuguese language and education in traditional way